Sulfur‐Infiltrated Micro‐ and Mesoporous Silicon Carbide‐Derived Carbon Cathode for High‐Performance Lithium Sulfur Batteries. (27th June 2013) - Lee, Jung Tae; Zhao, Youyang; Thieme, Sören; Kim, Hyea; Oschatz, Martin; Borchardt, Lars; Magasinski, Alexandre; Cho, Won‐Il; Kaskel, Stefan; Yushin, Gleb
<x xml:space="preserve">Abstract</x> Novel nanostructured sulfur (S)–carbide derived carbon (CDC) composites with ordered mesopores and high S content are successfully prepared for lithium sulfur batteries. The tunable pore‐size distribution and high pore volume of CDC allow for an excellent electrochemical performance of the composites at high current densities. A higher electrolyte molarity is found to enhance the capacity utilization dramatically and reduce S dissolution in S‐CDC composite cathodes during cycling. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>